Removal of Cr(VI) from Aqueous Environments Using Micelle-Clay Adsorption - Mohannad Qurie; Mustafa Khamis; Adnan Manassra; Ibrahim Ayyad; Shlomo Nir; Laura Scrano; Sabino A. Bufo; Rafik Karaman (The Scientific World Journal)
Removal of Cr(VI) from aqueous solutions under different conditions was investigated using either clay (montmorillonite) or micelle-clay complex, the last obtained by adsorbing critical micelle concentration of octadecyltrimethylammonium ions onto montmorillonite. Batch experiments showed the effects of contact time, adsorbent dosage, and pH on the removal efficiency of Cr(VI) from aqueous solutions. Langmuir adsorption isotherm fitted the experimental data giving significant results. Filtration experiments using columns filled with micelle-clay complex mixed with sand were performed to assess Cr(VI) removal efficiency under continuous flow at different pH values. The micelle-clay complex used in this study was capable of removing Cr(VI) from aqueous solutions without any prior acidification of the sample. Results demonstrated that the removal effectiveness reached nearly 100% when using optimal conditions for both batch and continuous flow techniques.